2016
DOI: 10.1002/2016gl067925
|View full text |Cite
|
Sign up to set email alerts
|

The signature of low‐frequency oceanic forcing in the Atlantic Multidecadal Oscillation

Abstract: The Atlantic Multidecadal Oscillation (AMO) significantly influences the climate of the surrounding continents and has previously been attributed to variations in the Atlantic Meridional Overturning Circulation. Recently, however, similar multidecadal variability was reported in climate models without ocean circulation variability. We analyze the relationship between turbulent heat fluxes and sea surface temperatures (SSTs) over the midlatitude North Atlantic in observations and coupled climate model simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
109
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(145 citation statements)
references
References 34 publications
24
109
2
Order By: Relevance
“…It is likely that atmosphere-ocean coupling plays a role in decadal variability in the North Atlantic sector (e.g., O'Reilly et al 2016). For example, Woollings et al (2015) found that decadal jet speed variability in a highresolution climate model was consistent with driving from subpolar gyre SST anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that atmosphere-ocean coupling plays a role in decadal variability in the North Atlantic sector (e.g., O'Reilly et al 2016). For example, Woollings et al (2015) found that decadal jet speed variability in a highresolution climate model was consistent with driving from subpolar gyre SST anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Clement et al (2015) argue that stochastic forcing from the atmosphere is the main source for the AMV, without any role for changes in ocean heat transport. Their article has attracted considerable attention, leading to several studies opposing their view (e.g., O'Reilly et al 2016;Zhang et al 2016;Drews and Greatbatch 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Variability in the Atlantic meridional overturning circulation (AMOC) has been linked to variability in Atlantic sea surface temperatures and associated climate impacts (Kushnir 1994;Delworth and Mann 2000;Knight et al 2005;O'Reilly et al 2016). There has been a significant number of studies aimed at understanding model-simulated AMOC variability in preindustrial or current climate conditions (Delworth et al 1993;Greatbatch and Zhang 1995;Yeager and Danabasoglu 2012); see also the recent review by Buckley and Marshall (2016).…”
Section: Introductionmentioning
confidence: 99%